Walking the Walk: Corporate Social Responsibility and Product Recalls in the Automotive Industry - Jebari, Fatima; Izaguirre-Lozano, Obed; Krishnaswami, Sudha; Lutey, Matthew M. (International Journal of Finance, 2024)
Purpose: The purpose of this paper is to disentangle a unique way in which corporate social responsibility (CSR) affects firm value in the context of product recalls in the automotive industry. Methodology: Using a sample of product recall events in the automotive industry between 2002 and 2018 and controlling for the spread of product recalls across product lines, this study explores the underlying economic channels through which CSR improves investments in quality. For robustness check, self-selection bias is corrected for using a 2SLS approach and alternative measures for product failures and CSR. Findings: The authors find that firms with higher CSR scores are associated with a lower frequency of recalls. Moreover, higher CSR scores are associated with a higher likelihood of voluntary recalls, higher product quality, higher capital expenditures, and higher employee productivity. Unique Contribution to Theory, Practice, and Policy: This study offers insights to managers, investors, and board members, showing the potential benefits of engaging in CSR activities. This study contributes to the literature on the effect of CSR on different managerial decisions and the factors that affect product recalls. Additionally, the study reveals the connection between CSR and product recalls.